High-purity and high-strength stainless steel bar for hydraulic system and preparation method of high-purity and high-strength stainless steel bar
By optimizing the composition and smelting process in stainless steel rods, cracking and leakage problems of existing stainless steel rods in high pressure and corrosion environments are solved, and high tensile strength, yield strength and elongation, as well as high corrosion resistance are achieved.
Patent Information
- Application Number
- CN202311259059.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing stainless steel bars used in hydraulic systems have cracking and leakage problems in high pressure and corrosive environments, which affect the use and safety of the equipment.
High-purity and high-strength stainless steel rods are used, and their components include C, Si, Cr, Mn, Mo, Ni, Cu, Nb and other elements. Through strict control of components and smelting processes, the δ ferrite content is reduced, and the grain size and thermal processing performance of the material are improved.
It achieves high tensile strength, yield strength and elongation of stainless steel rods, ensures the material's heterogeneous consistency and high corrosion resistance, and is suitable for hydraulic systems and other high-demand fields.
Smart Images

Figure BDA0004472161880000111 
Figure BDA0004472161880000121 
Figure BDA0004472161880000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of stainless steel bar processing, and in particular relates to a high-purity and high-strength stainless steel bar for a hydraulic system and a preparation method thereof. Background Art
[0002] In the field of mechanical engineering, hydraulic cylinders are important components that convert hydraulic energy into mechanical energy. They are generally made of high-quality carbon structural steel or low-alloy structural steels such as MnMo, SiMn, and CrMo. However, the above materials have poor corrosion resistance and cannot be used for long-term use in marine engineering machinery with severe corrosion. In addition, in addition to being subjected to the effects of high-pressure liquids, hydraulic cylinders must also consider the corrosion damage of the hydraulic medium to the inner wall of the cylinder body, and the wear of the plunger or piston and the inner wall of the cylinder body. Therefore, large and medium-sized hydraulic cylinders with high service environment requirements generally require high strength and good toughness of the cylinder body material, and are often made of precipitation-hardened stainless steel.
[0003] Precipitation hardening stainless steel is generally achieved by adding hardening elements to precipitate fine intermetallic compounds and some small amounts of carbides during the aging heat treatment process to achieve a hardening effect, thereby obtaining high strength, high toughness and high corrosion resistance. Martensitic precipitation hardening stainless steel is usually in service in the martensitic state, and its performance can be obtained through the formation of martensite and the combined action of one or both of the precipitation hardening mechanisms. Its mechanical properties can also be adjusted within a fairly wide range by changing the aging temperature. Because it uses martensitic phase transformation and precipitation hardening mechanisms, it makes up for the shortcomings of low strength of austenitic steel and reduced corrosion resistance after martensitic steel is heat treated to high strength.
[0004] The commonly used martensitic precipitation hardening stainless steel is 0Cr17Ni4Cu4Nb (GB / T1220-2007). This steel is designed with low C, high Cr and Cu. Its strength, toughness and corrosion resistance are better than those of general martensitic stainless steel, but its process performance is relatively poor, mainly because the steel contains 5-10% delta ferrite (ferrite formed at high temperature). The presence of delta ferrite will affect the thermoplasticity of the steel, reduce the strength of the steel and deteriorate the transverse toughness of the steel, and also reduce the corrosion resistance of the steel.
[0005] Chinese patent CN105714063B discloses "a method for preparing 0Cr17Ni4Cu4Nb precipitation hardened stainless steel bar", whose components include: Ni: 3~5wt%, Cr: 15.5~17.5wt%, Cu: 3~5wt%, Nb: 2.5~4.5wt%, and the rest is Fe. The tensile strength of the bar is ≥1550MPa and the surface hardness reaches HRC47.
[0006] Chinese patent CN200810034926.7 discloses "a kind of martensitic precipitation hardening stainless steel for structural parts and its manufacturing method", the chemical composition includes: C≤0.05wt%, Cr: 13.50~15.50wt%, Cu: 2.5~4.0wt%, Ni: 3.0~5.0wt%, Nb+Ta: 0.15~0.40wt%, N: 0.010~0.040wt%, V: 0.050~0.15wt%, Si≤0.80wt%, Mn≤1.00wt%, P≤0.025wt%, S≤0.010wt%, the balance is Fe and unavoidable impurities. The tensile strength of stainless steel reaches 1390Mpa, the yield strength reaches 1300Mpa, the elongation reaches 15%, and the shrinkage reaches 48% (transverse performance).
[0007] The high-strength stainless steel disclosed in the above two patents is a precipitation-hardened stainless steel bar reinforced with Cu element and its preparation method, and a precipitation-hardened stainless steel rod with high strength, high toughness and high corrosion resistance is manufactured through vacuum melting ingot, forging blanking, extrusion deformation, etc. However, due to the insufficient purity of molten steel and the presence of many non-metallic inclusions in the steel, cracking and leakage problems often occur when hydraulic cylinder parts are manufactured using the above method, affecting the use and safety of the equipment. Summary of the invention
[0008] The purpose of the present invention is to provide a high-purity and high-strength stainless steel bar for a hydraulic system and a preparation method thereof. The stainless steel bar has a tensile strength of not less than 1350MPa, a delta ferrite content of ≤0.45%, a grain size of ≥7 levels, and a transverse and longitudinal shrinkage difference of ≤5%, thereby ensuring the isotropic consistency of the mechanical properties of the material, improving the hot processing performance of the material, and being easy to process. The stainless steel bar can be used in the hydraulic field with high requirements on strength, plasticity and corrosion resistance, and can also be used in the fields of aerospace, petroleum, chemical industry, energy and power.
[0009] To achieve the above object, the technical solution of the present invention is:
[0010] A high-purity and high-strength stainless steel bar for hydraulic systems, the composition weight percentage of which is: C: 0.03-0.05%, S≤0.01%, P≤0.03%, Si: 0.20-0.60%, N≤0.01%, O≤0.001%, Cr: 14.00-15.00%, Mn: 0.40-0.70%, Mo: 0.10-0.50%, the balance includes Fe and other inevitable impurities, and needs to meet the following requirements at the same time:
[0011] 4.50%≤Ni+Mn / 2≤5.80%;
[0012] Cu=Cr / 3.9-0.2;
[0013] Nb = 7.75 × C + 0.05.
[0014] Furthermore, the ratio of Ni equivalent / Cr equivalent is ≥0.42, wherein the calculation formulas of Ni equivalent and Cr equivalent are as follows:
[0015] Ni eq(%)=Ni+0.5Mn+33C+26N+0.3Cu;
[0016] Cr eq(%)=Cr+1.6Si+Mo+0.6Nb.
[0017] Furthermore, the balance is Fe and other inevitable impurities.
[0018] The content of delta ferrite in the microstructure of the stainless steel bar of the present invention is ≤0.45%, and the grain size is ≥7 levels.
[0019] The stainless steel bar of the present invention has a tensile strength of ≥1350MPa, a yield strength of ≥1300MPa, an elongation of ≥12%, and a surface shrinkage of ≥40%.
[0020] In the composition design of the present invention:
[0021] Carbon (C): It is an interstitial solid solution element that stabilizes austenite, inhibits the formation of delta ferrite, and can form fine dispersed carbides, which can significantly improve the matrix strength of steel. However, its solubility in austenite and ferrite is limited. Too high a carbon content will reduce the toughness of the steel and will cause precipitation of M during heat treatment. 23 C6 carbides reduce the intergranular corrosion resistance of steel. However, too low a carbon content can easily lead to a decrease in the precipitation temperature of carbides. During solution heat treatment, the grains lacking carbide pinning are prone to grow due to the premature dissolution of carbides, thereby affecting the impact toughness of stainless steel. Therefore, the carbon content in the present invention is controlled at 0.03-0.05%.
[0022] Silicon (Si): It is mainly used as a deoxidizer during smelting, and can strengthen the matrix, improve the corrosion resistance and high temperature oxidation resistance of steel. However, too high a silicon content will lead to the precipitation of harmful phases, reducing the hot working performance and toughness of the steel. Therefore, the silicon content of the present invention is controlled at 0.20-0.60%.
[0023] Chromium (Cr): It is a ferrite stabilizing element. It mainly improves the corrosion resistance and oxidation resistance of stainless steel. Studies have shown that steel must contain at least 10.5% Cr to form a stable passivation film that protects the steel from atmospheric corrosion. The corrosion resistance of stainless steel increases with the increase of Cr content. However, too high Cr content will promote the formation of delta ferrite phase, reduce the hot working performance of stainless steel and the longitudinal and transverse consistency at room temperature, and easily lead to metal segregation during smelting. Therefore, the chromium content of the present invention is controlled at 14.00-15.00%.
[0024] Manganese (Mn): It is an austenite stabilizing element that can expand the austenite phase. It is a good deoxidizer and desulfurizer. Industrial steel usually contains a certain amount of manganese. In stainless steel, manganese can replace part of nickel to stabilize austenite, reduce production costs, and increase the nitrogen content in steel to ensure the strength of steel. However, too high manganese content will greatly reduce the corrosion resistance of steel, especially the ability to resist pitting and intergranular corrosion. Therefore, the manganese content of the present invention is controlled at 0.40-0.70%.
[0025] Nickel (Ni): It is an austenite stabilizing element that can expand the austenite phase region, thereby ensuring that the stainless steel has good plastic deformation characteristics. An increase in nickel content can effectively reduce the δ ferrite content. Nickel can improve the composition, structure and properties of the chromium oxide film, thereby improving the corrosion resistance and oxidation resistance of stainless steel. In addition, it can significantly reduce the cold working hardening tendency of stainless steel, but too high a nickel content will lead to an increase in production costs. Considering that nickel and manganese are both austenite forming elements, and the austenite forming ability of Mn is about twice that of nickel, plus the suppression of δ ferrite precipitation must be considered, and the nickel equivalent and chromium equivalent need to be matched. Taking all factors into consideration, the total nickel and manganese content of the present invention is controlled to 4.50%≤Ni+Mn / 2≤5.80%.
[0026] Copper (Cu): It is the main precipitation strengthening element in stainless steel. Through solution aging heat treatment, dispersed ε-copper-rich phase is precipitated in the martensite matrix to produce precipitation hardening and strengthen the steel. Appropriately increasing the copper content in steel can reduce the δ-ferrite content in steel; copper is also a weak austenite-forming element. In a corrosive environment, steel containing copper elements can form a copper aggregation layer under the protection of the oxide layer, which can effectively prevent iron oxide from continuing to corrode the inside of the metal and prevent corrosion from spreading. Therefore, adding copper to martensitic aging stainless steel can improve the corrosion resistance of steel in sulfuric acid and hydrochloric acid. Adding copper elements can also enhance the ability of steel to resist stress corrosion. In addition, according to the inventor's experience, it is found that after the Cu content exceeds a certain value, the strength of the alloy cannot be significantly improved, and too high a Cu content is prone to component segregation, which is easy to cause local overburning during the production heating process. Therefore, it is necessary to strictly control the Cu content in the alloy. In the present invention, it is considered that Cu and Cr elements are combined to form an ε-copper-rich strengthening phase. The energy spectrum analysis shows that the molar atomic ratio of the two is about 1:2, and the matrix needs to ensure the presence of solid solution Cr elements not less than the Cr content in the strengthening phase. However, the actual results show that the alloying effect of the product obtained in full accordance with this ratio is still not ideal. The present invention corrects the coefficient of Cr and adds a constant coefficient of -0.2 to obtain a new empirical formula Cu=Cr / 3.9-0.2, which can ensure that all the generated copper can exist in the ε-copper-rich strengthening phase, avoiding component segregation caused by excessive addition of copper elements.
[0027] Molybdenum (Mo): It is beneficial to the strength, toughness and corrosion resistance of martensitic stainless steel. When molybdenum-rich precipitates are precipitated in the early stage of aging, they can not only play a strengthening role, but also maintain the toughness of steel, which plays an important role in the strengthening and toughening of steel. The presence of molybdenum can also hinder the precipitation of precipitated phases on the original austenite grain boundaries, avoid intergranular fracture, and improve the fracture toughness of steel. In some reducing media, molybdenum can also promote the passivation of Cr. Therefore, molybdenum can improve the corrosion resistance of chromium-nickel stainless steel in some reducing acids, such as sulfuric acid, hydrochloric acid, phosphoric acid and some organic acids, and can effectively inhibit the pitting corrosion tendency of chloride ions on steel, and improve the ability to resist intergranular corrosion. Since molybdenum, like nickel, is also an austenite-forming element, the molybdenum element cannot be excessive. Excessive addition will generate residual austenite, thereby affecting the tensile strength. Therefore, the molybdenum content of the present invention is controlled at 0.10-0.50%.
[0028] Niobium (Nb): It is a strong carbide-forming element, which can form fine and dispersed NbC, Nb (C, N) and other carbides with carbon in the matrix. These precipitated phases have good stability, which plays an important role in maintaining the stability of the sub-grain structure and improving the long-term strength of steel, and greatly improves the tempering resistance of steel. In order to give full play to the precipitation strengthening effect of niobium carbides, it is necessary to control Nb = 7.75 × C + 0.05. Theoretically, the atomic molar ratio of niobium (Nb) and carbon (C) is 7.75, but the actual results show that the alloying effect of the product obtained by this ratio is not ideal, and it is necessary to appropriately increase the niobium content to form carbide pinning to refine the grains.
[0029] Studies have shown that in order to improve the toughness of stainless steel under ultra-high strength conditions (≥1350MPa), and to have high purity and fine and uniform grain size, the content of impurity elements needs to be strictly controlled: S≤0.01%, P≤0.03%, N≤0.01%, O≤0.001%, H≤0.0001%.
[0030] Sulfur (S): It exists in the form of FeS in steel, which will cause the hot brittleness of steel. The melting point of FeS is 1193℃, while the melting point of the eutectic composed of Fe and FeS is only 985℃. Liquid Fe and FeS can be infinitely soluble in each other, but the solubility of FeS in solid iron is very small, only 0.015-0.020%. Therefore, when the sulfur content of steel exceeds 0.020%, due to segregation during the cooling and solidification process of the molten steel, Fe-FeS is distributed in the grain boundaries in a network in the form of a low-melting-point eutectic. The hot working temperature of steel is between 1150 and 1200℃. At this temperature, the eutectic at the grain boundary has melted. When the steel is compressed, it causes the rupture of the grain boundary. This is the "hot brittleness" of the steel. When the oxygen content in the steel is high, the melting point of the eutectic formed by FeO and FeS is lower, only 940℃, which aggravates the "hot brittleness" phenomenon of the steel. In addition, sulfur will significantly reduce the welding performance of steel, cause high temperature cracking, and produce many pores and looseness in the metal weld, thereby reducing the strength of the weld. When the sulfur content exceeds 0.06%, the corrosion resistance of the steel is significantly deteriorated. Therefore, the sulfur content of the present invention is controlled to be below 0.01%.
[0031] Phosphorus (P): can be completely dissolved in ferrite, improving the strength and hardness of ferrite. However, at room temperature, it causes a sharp drop in the plasticity and toughness of steel, resulting in low-temperature brittleness, a phenomenon known as cold brittleness. Generally speaking, phosphorus is a harmful element in steel, mainly precipitating the brittle compound Fe3P, which increases the brittleness of steel, especially at low temperatures. Therefore, the phosphorus content of the present invention is controlled to be below 0.03%.
[0032] Nitrogen (N): It exists in the form of interstitial atoms in the unit cell. Due to the large difference in atomic size, it is more conducive to the solid solution strengthening of steel. As an austenite stabilizing element, N has an effect of about 25 times that of Ni on expanding and stabilizing austenite structure. Its solid solubility content in austenite is much higher than that of ferrite. Usually, there is a small amount of ferrite in conventional stainless steel. As the carbon content decreases, the ferrite content will increase, resulting in a decrease in the strength, plasticity and toughness of the stainless steel. Therefore, the nitrogen content of the present invention is controlled to be below 0.01%.
[0033] Hydrogen (H): It is a harmful element in steel. Hydrogen dissolved in steel can cause defects such as hydrogen embrittlement and white spots. Hydrogen has a very low solubility in solid steel. It dissolves into molten steel at high temperature. When cooling and solidifying, it has no time to escape and accumulates in the steel matrix to form high-pressure fine pores, which sharply reduce the plasticity, toughness and fatigue strength of the steel. In severe cases, it can cause cracks and brittle fractures. Therefore, the hydrogen content of the present invention is controlled to be below 0.0001%.
[0034] Oxygen (O): It will have an adverse effect on the mechanical properties of steel. Not only the concentration of oxygen, but also the amount, type and distribution of oxygen-containing inclusions have a very important influence. Oxygen-containing inclusions refer to metal oxides, silicates, aluminates, oxygen-containing sulfides and similar inclusion compounds. Deoxidation is required in steelmaking because during solidification, oxygen and carbon in the solution react to produce carbon monoxide, which can cause bubbles. In addition, during cooling, oxygen can precipitate from the solution as FeO, MnO and other oxide inclusions, thereby weakening its hot or cold workability, as well as ductility, toughness, fatigue strength and mechanical processing properties of steel. Therefore, the oxygen content of the present invention is controlled below 0.001%.
[0035] In order to achieve high strength and good corrosion resistance, elements such as Cr, Ni, Mo, and Cu are added in the present invention. In order to ensure good toughness while having ultra-high strength (≥1350MPa), in addition to requiring a very low impurity content and ensuring high purity, the steel also needs to have a fine and uniform grain structure (≥7 levels). For this reason, the present invention retains a small amount of carbon in the steel and adds a small amount of Nb to form carbide pinning to ensure that the grains will not grow during the heat treatment process.
[0036] Since the Cr content of the present invention is relatively high, a considerable amount of residual δ ferrite will be produced. A large number of studies have shown that the δ ferrite content is the main reason for the large longitudinal and transverse differences in mechanical properties such as tensile strength and fracture toughness. In order to improve the isotropic consistency of the mechanical properties of the present invention, it is necessary to reduce the δ ferrite content as much as possible (≤0.45%), and it is necessary to control the ratio of Ni equivalent to Cr equivalent to ≥0.42. However, the control of the stainless steel structure of the present invention according to the commonly used Schaeffler diagram and Delong diagram is not ideal. Therefore, the present invention modifies the formulas involved in the above two diagrams according to the experience and data accumulation of the inventor. The C and N contents of the present invention are lower than those of conventional stainless steel. Therefore, compared with the conventional Ni equivalent formula, the coefficient of C in the new formula is reduced from 35 to 33, and the coefficient of N is reduced from 30 to 26. Cu is the main strengthening element in the present invention, and its content is higher than that of conventional stainless steel, so the coefficient of Cu is increased from 0.25 to 0.3. In addition, the Si and Nb contents in the present invention are higher than those in conventional stainless steel, so the Si coefficient in the Cr equivalent formula increases from 1.5 to 1.6, and the Nb coefficient increases from 0.5 to 0.6. A new empirical formula is formed to control the chemical composition, wherein the Ni equivalent is calculated according to the formula Ni eq (%) = Ni + 0.5Mn + 33C + 26N + 0.3Cu, and the Cr equivalent is calculated according to the formula Creq (%) = Cr + 1.6Si + Mo + 0.6Nb.
[0037] The method for preparing the high-purity and high-strength stainless steel bar that can be used in the hydraulic system of the present invention comprises the following steps:
[0038] 1) Smelting and casting
[0039] According to the above composition smelting, raw iron with purity ≥ 99.9% and other pure metals are used as furnace charge, and the charge is melted by induction heating in a vacuum environment below 3Pa. The molten steel needs to be continuously stirred by electromagnetic + gas mixed stirring in a high-temperature refining stage of 1500-1600℃. Subsequently, the high-purity molten steel obtained above is poured into a cylindrical ingot mold in a vacuum environment to obtain an electrode rod;
[0040] The electrode rod is purified in a copper crucible in a vacuum environment below 5 Pa by melting and solidifying. During the purification process, the inner and outer walls of the crucible are cooled by a composite cooling method of air cooling and water cooling to obtain a stainless steel ingot.
[0041] 2) Billet forging
[0042] The stainless steel ingot is heated to 1200-1250°C and kept warm for ≥15h, and then forged to obtain an intermediate forging billet;
[0043] 3) Forging or rolling
[0044] The intermediate forging billet is heated to 1050-1090°C, and the stainless steel bar is obtained by forging or rolling, and the total deformation ratio of the finished product is ≥6;
[0045] 4) Solution treatment and cooling
[0046] The solution heating temperature is 1020~1060℃, and the holding time is ≥1h. After the holding time is over, the furnace is taken out and quenched and cooled to below 30℃;
[0047] 5) Aging heat treatment
[0048] The aging heating temperature is 475-495℃, and the holding time is 1-10h. After the holding period, the product is taken out of the furnace and air-cooled to room temperature.
[0049] In the preparation process design of the present invention:
[0050] In order to obtain high-purity ingots, the measures taken are mainly:
[0051] 1) In order to reduce the inclusions of type A (sulfide) and type C (silicate), self-made Cr-containing high-purity raw iron with low S content and other pure metals are used as charge materials, and the charge materials are melted by induction heating in a vacuum environment below 3Pa.
[0052] 2) In order to quickly and thoroughly remove oxygen and nitrogen from the molten steel and reduce Class B (oxides) and Class D (spherical oxides and nitrides) inclusions, the molten steel needs to be continuously stirred using an electromagnetic + gas mixed stirring method during a high-temperature refining stage at 1500-1600°C.
[0053] 3) To avoid gas pollution, the high-purity molten steel obtained above is poured into a cylindrical steel ingot mold in a vacuum environment to obtain an electrode rod.
[0054] 4) To further improve the purity of the steel, the electrode rod is purified by melting and solidifying in a copper crucible in a vacuum environment below 5 Pa.
[0055] 5) During the purification process, the inner and outer walls of the crucible are cooled by inert gas and laminar water respectively to improve the cooling efficiency, so that the molten steel in the molten pool is quickly cooled and solidified, thereby obtaining a high-purity, defect-free, dense, fine-grained steel ingot.
[0056] In the preparation method of the present invention, in order to reduce the delta ferrite produced during the production process and improve the hot working performance of the material and the longitudinal and transverse consistency at room temperature, the measures taken mainly include:
[0057] During the open forging process, the ingot is heated to 1200-1250℃ and kept warm for no less than 15 hours. The residual δ ferrite in the ingot caused by non-equilibrium solidification is eliminated by solid high temperature equilibrium diffusion, and then the open forging is performed to obtain the intermediate billet. This can effectively control and eliminate the δ ferrite in the matrix.
[0058] In the preparation method of the present invention, in order to improve strength and toughness, it is necessary to obtain a fine and uniform grain structure, and the measures taken are mainly:
[0059] 1) The intermediate forging billet is heated to 1050-1090°C, and fully deformed by forging or rolling, and the total deformation ratio of the finished product is ≥6.
[0060] 2) When the product is subjected to solution heat treatment, in order to ensure that the grains are fully recrystallized and do not grow, the solution temperature is controlled at 1020-1060°C and the holding time is not less than 1 hour. Low temperature will affect the solution effect and reduce the uniformity of the structure. Too high temperature will lead to coarse grains and affect the plasticity and toughness of the material.
[0061] Since the alloying elements and contents of the present invention are relatively high, and the martensitic transformation temperature is relatively low, if the cooling after solid-state heat treatment is insufficient, a large amount of residual austenite will exist in the steel, which will reduce the strength of the steel. Therefore, the present invention strictly controls the temperature after cooling out of the furnace to be within the martensitic transformation end temperature M. f However, the martensitic transformation temperature obtained according to the existing martensitic transformation temperature calculation formula has a large error in the present invention. Therefore, the martensitic transformation end temperature M calculated according to the previous calculation formula is f If the temperature is controlled, there may be insufficient cooling. After research, the present invention corrects the calculation formula of the martensitic transformation temperature so as to control the temperature more accurately.
[0062] Since the present invention is an ultra-low carbon ultra-pure martensitic precipitation hardening stainless steel, the content of C, Mn, Si, N, etc. is low, which has no effect on the martensitic transformation temperature, so no excessive consideration is given during calculation. In addition, considering that most studies on martensitic transformation temperature are mainly based on low-alloy structural steel, a new empirical formula is formed: Ms = 1280-45Cr-62Ni-30Mo-28Si-35Mn-15Nb-27Cu, and the martensitic transformation end temperature Mf = Ms-120,
[0063] Furthermore, within the chemical composition range of each element involved in the present invention, the martensitic transformation start temperature Ms is generally controlled above 165°C, and the martensitic transformation end temperature Mf is controlled above 45°C. Considering the temperature fluctuation caused by the chemical composition deviation in the actual production process, in order to reduce the risk of non-conformity, in actual production, the material will be cooled to below 30°C on the basis of cooling to 45°C, so as to reduce and eliminate the influence of retained austenite on tensile strength.
[0064] In the subsequent aging heat treatment process, in order to ensure that the copper-rich strengthening phase can be dispersed and precipitated to fully play a strengthening role, the aging temperature is controlled at 475-495°C and the holding time is 1-10 hours. If the temperature is too low and the time is too short, the strengthening phase cannot be dispersed and precipitated, which reduces the strengthening effect and fails to achieve the expected strength. If the temperature is too high and the time is too long, it is easy to cause the precipitate to coarsen and grow, and the ideal strengthening effect cannot be achieved.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] 1. The present invention uses Cu as the main strengthening element for precipitation hardening strengthening in terms of composition, combines the addition of Nb element, and utilizes the composite strengthening method of precipitation strengthening plus carbide strengthening to obtain higher strength. At the same time, by strictly controlling the content of Cu, satisfying Cu=Cr / 3.9-0.2, Cu is made to exist in the form of ε-rich copper strengthening phase, avoiding the element segregation caused by excessive addition of Cu element, which affects the hot working performance of the material. Combined with the addition of Ni and Mn elements, and controlling the ratio of Ni equivalent / Cr equivalent ≥0.42, the δ ferrite content is reduced, so that the stainless steel bar can obtain ultra-high strength and high toughness while reducing the longitudinal and transverse plasticity differences. In addition, the present invention strictly limits the content of S, P, Si, Mn, N, Ti, H, and O elements to improve the plasticity of the bar. Although conventional ultra-high strength steel strengthened with copper can also achieve higher strength, it does not consider the influence of processing performance and plasticity, and cannot control the impurity elements within such a low range.
[0067] 2. Based on the composition design, the present invention adopts relatively high purity raw materials to be smelted under vacuum conditions during the smelting process, and adopts electromagnetic + gas mixing and stirring to quickly and thoroughly remove oxygen and nitrogen from the molten steel during the smelting process, thereby avoiding the generation of impurities during the smelting process. Subsequently, through purification and rapid cooling, a high-purity, defect-free, dense, fine-grained steel ingot is obtained, thereby improving the toughness of stainless steel. Subsequently, a higher heating temperature (1200-1250°C) and a precise heat treatment control system are adopted to effectively control and eliminate the delta ferrite in the matrix through solid-state high-temperature equilibrium diffusion, thereby improving the isotropic consistency of the material.
[0068] 3. The high-strength stainless steel bar of the present invention has a transverse tensile strength of ≥1350MPa, a yield strength of ≥1300MPa, an elongation of ≥12%, a surface shrinkage of ≥40%, and a transverse and longitudinal surface shrinkage difference of ≤5%. Due to its excellent corrosion resistance and mechanical properties, it can be applied to the hydraulic field with high requirements for strength, toughness and corrosion resistance, and can also be applied to the fields of aerospace, petroleum, chemical industry, energy and power. Especially in the field of aerospace, the use of high-strength stainless steel instead of traditional high-strength steel not only increases the service life of aircraft and shortens the maintenance cycle, but also reduces manufacturing costs and reduces environmental pollution. DETAILED DESCRIPTION
[0069] The present invention will be further described below in conjunction with the embodiments.
[0070] The composition of the steel of the embodiment of the present invention is shown in Table 1, and the remainder of the composition is Fe and other inevitable impurities; Table 2 shows the preparation process parameters of the steel of the embodiment of the present invention, and Table 3 shows the performance parameters of the steel of the embodiment of the present invention.
[0071] In Comparative Example 1, an ingot is obtained by smelting in an electric furnace + electroslag. Since the smelting is carried out in the atmosphere, the content of various impurities is relatively high. Therefore, it can be seen from the test results in Table 3 that the size and content of the inclusions are relatively high. If this type of inclusion is used to manufacture hydraulic cylinder components, component cracking and leakage problems are likely to occur, affecting the use and safety of the equipment.
[0072] In comparative example 2, an ingot is obtained by smelting in an electric furnace. Since the ratio of Ni equivalent / Cr equivalent in chemical composition is less than 0.42, and the heating and forging temperature of the ingot is relatively low compared with the present invention, the delta ferrite content is as high as 5%, and the transverse and longitudinal mechanical properties of the material are quite different. Moreover, since the smelting is carried out in the atmosphere, the content of various impurities is relatively high. Therefore, it can be seen from the test results in Table 3 that the size and content of the inclusions are relatively high. If this type of material is used to manufacture hydraulic cylinder components, it is easy to cause component cracking and leakage problems, which affects the use and safety of the equipment.
[0073] The high-strength stainless steel bar material of the present invention can be applied to the hydraulic field with high requirements on strength, toughness and corrosion resistance due to its excellent corrosion resistance and mechanical properties, and can also be applied to the fields of aerospace, petroleum, chemical industry, energy and power. Especially in the field of aerospace, the use of high-strength stainless steel instead of traditional high-strength steel not only increases the service life of the aircraft, shortens the maintenance cycle, but also reduces the manufacturing cost and reduces environmental pollution.
[0074]
[0075]
[0076]
Claims
1. A high-purity and high-strength stainless steel bar that can be used in a hydraulic system, the composition weight percentage of which is: C: 0.03-0.05%, S≤0.01%, P≤0.03%, Si: 0.20-0.60%, N≤0.01%, O≤0.001%, Cr: 14.00-15.00%, Mn: 0.40-0.70%, Mo: 0.10-0.50%, the balance includes Fe and other inevitable impurities, and needs to meet the following requirements at the same time: 4.50%≤Ni+Mn / 2≤5.80%; Cu=Cr / 3.9-0.2; Nb = 7.75 × C + 0.
05.
2. The high-purity and high-strength stainless steel bar that can be used in hydraulic systems according to claim 1, characterized in that: The ratio of Ni equivalent / Cr equivalent is ≥0.42, where the calculation formulas for Ni equivalent and Cr equivalent are as follows: Ni eq(%)=Ni+0.5Mn+33C+26N+0.3Cu; Cr eq(%)=Cr+1.6Si+Mo+0.6Nb.
3. The high-purity and high-strength stainless steel bar material that can be used in hydraulic systems according to claim 1 or 2, characterized in that: The balance is Fe and other inevitable impurities.
4. The high-purity and high-strength stainless steel bar material for hydraulic systems as claimed in claim 1, 2 or 3, characterized in that: The content of delta ferrite in the microstructure of the stainless steel bar is ≤0.45%, and the grain size is ≥7 levels.
5. The high-purity and high-strength stainless steel bar material for hydraulic systems as claimed in claim 1, 2, 3 or 4, characterized in that: The stainless steel bar has a transverse tensile strength of ≥1350 MPa, a yield strength of ≥1300 MPa, an elongation of ≥12%, a surface shrinkage of ≥40%, and a transverse and longitudinal surface shrinkage difference of ≤5%.
6. The method for preparing the high-purity and high-strength stainless steel bar that can be used in hydraulic systems according to any one of claims 1 to 5, comprising the following steps: 1) Smelting and casting According to the composition smelting of claim 1, 2 or 3, raw iron with purity ≥99.9% and other pure metal elements are used as furnace charge, and the furnace charge is melted by induction heating in a vacuum environment below 3Pa. The molten steel needs to be continuously stirred by electromagnetic + gas mixed stirring in a high-temperature refining stage of 1500-1600°C. Subsequently, the high-purity molten steel obtained above is poured into a cylindrical ingot mold in a vacuum environment to obtain an electrode rod; The electrode rod is purified in a copper crucible in a vacuum environment below 5 Pa by melting and solidifying. During the purification process, the inner and outer walls of the crucible are cooled by a composite cooling method of air cooling and water cooling to obtain a stainless steel ingot. 2) Billet forging The stainless steel ingot is heated to 1200-1250°C and kept warm for ≥15h, and then forged to obtain an intermediate forging billet; 3) Forging or rolling The intermediate forging billet is heated to 1050-1090°C, and the stainless steel bar is obtained by forging or rolling, with a total deformation ratio of ≥6; 4) Solution treatment and cooling The solution temperature is 1020~1060℃, and the solution time is ≥1h. After the heat preservation is completed, it is taken out of the furnace and cooled to the martensitic transformation end temperature M f Below, M f =M s -120, M s =1280-45Cr-62Ni-30Mo-28Si-35Mn-15Nb-27Cu; 5) Aging heat treatment The aging temperature is 475-495℃, and the aging time is 1-10h. After the insulation is completed, the steel is taken out of the furnace and air-cooled to room temperature.
7. The preparation method according to claim 6, characterized in that: In step 4), the mixture is cooled to below 30° C. after being taken out of the furnace.
Citation Information
Patent Citations
Martensite precipitation hardening stainless steel for structural member and manufacturing method thereof
CN101538686B
Preparation method of a 0Cr17Ni4Cu4Nb precipitation hardening stainless steel bar
CN105714063B